On Current Sheets and Associated Density Spikes in Titan's Ionosphere as Seen From Cassini. Issue 3 (27th February 2023) - Kim, Konstantin; Edberg, Niklas J. T.; Shebanits, Oleg; Wahlund, Jan‐Erik; Vigren, Erik; Bertucci, Cesar
Abstract: The Cassini spacecraft made in‐situ measurements of Titan's plasma environment during 126 close encounters between 2004 and 2017. Here we report on observations from the Radio and Plasma Waves System/Langmuir probe instrument (RPWS/LP) from which we have observed, primarily on the outbound leg, a localized increase of the electron density by up to 150 cm −3 with respect to the background. This feature, appearing as an electron density spike in the data, is found during 28 of the 126 flybys. The data from RPWS/LP, the electron spectrometer from the Cassini Plasma Spectrometer package, and the magnetometer is used to calculate electron densities and magnetic field characteristics. The location of these structures around Titan with respect to the nominal corotation direction and the sun direction is investigated. We find that the electron density spikes are primarily observed on the dayside and ramside of Titan. We also observe magnetic field signatures that could suggest the presence of current sheets in most cases. The density spikes are extended along the trajectory of the spacecraft with the horizontal scale of ∼537 ± 160 km and vertical scale ∼399 ± 163 km. We suggest that the density spikes are formed as a result of the current sheet formation. Key Points: Electron density spikes of up to ∼150 cm −3 from RPWS/LP data are observed during the outbound leg of the Cassini's Titan encounters The correlation between the density spikes and a decrease of the magnetic field strength is consistent with the presence of a current sheet The analysis of 126 encounters reveals the presence of these enhancements in 28 cases